Вивчення боротьби селянства Правобережної України проти духовенства в пореформений період (1861–1900 рр.) у працях Д. П. Пойди - Кучерук, О. (Схід, 2009)
Стаття присвячена аналізу наукового доробку професора Д. П. Пойди з історії селянських виступів Правобережної України проти сільського духовенства в пореформений період (1861-1900 рр.). Автор статті дійшов висновку, що Д. П. Пойда на основі джерел дослідив
характер взаємин селян та духовенства, роль служителів церкви у впровадженні реформи
1861 р. у Київській, Подільській та Волинській губерніях, особливості статусу духовенства
Правобережної України; спираючись на конкретні приклади, визначив причини, методи та
результати боротьби селянства проти духовенства. Таким чином, Д. П. Пойда зробив вагомий внесок у дослідження соціально-аграрної історії України другої половини ХІХ ст. The article is devoted to analysis of scientific works of professor D. P. Pojda to the history of peasants' revolts in
Right-bank Ukraine against rural clergy in the post-reform period (1861-1900). The author of the article has come to
conclusion that D. P. Pojda on the basis of sources investigated the character of relations of peasantry and clergy, the
priests' role in realization of reform in 1861 in Kyiv, Podolsk and Volynsk province, the feature of the status of clergy in
Right-bank Ukraine; he is leaning against concrete examples, he has advanced the reasons, methods and results of
peasantry's struggle against clergy. Thus, D. P. Pojda has made the important investment in the research of social agrarian history of Ukraine in the second half of XIX-th century.